Identification of Nutritional Status and Patient Diseases in Pediatric Inpatient Room at Pekalongan District Hospital - Ristanti Ristanti; Siti Rofiqoh (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Malnutrition status in children can cause various problems including decreased immune system so that children are susceptible to infection. Infectious diseases are the highest cases experienced by children in the hospital's pediatric inpatient room. Infection in children also raises the risk of children experiencing malnutrition. This study aims to identify the nutritional status and disease of patients in the pediatric inpatient room. The study was conducted in the pediatric inpatient ward of the RSUD in Pekalongan Regency. The research design used descriptive cross-sectional. Samples were children who were treated in the pediatric inpatient room at Kajen Hospital and Kraton Pekalongan Hospital. The sampling technique used consecutive sampling with a time of 6 months and obtained 153 respondents. The research instrument used a questionnaire of respondents' characteristics, the patient's disease data was taken based on medical diagnosis data from the patient's medical record. Nutritional status in patients aged < 5 years was based on body weight for age (W/U), patients > 5 years was based on body mass index for age (BMI/U). Nutritional status was categorized based on the threshold (Z-score). The results showed that the first and second most cases of disease were diarrhea (51%) and Acute Respiratory Infection (ARI) (30%), the most nutritional status was normal (60.1%), 16.3% malnutrition and 11.8% poor nutrition and 11, 8% fat. The conclusion is that the two most cases in children in the pediatric inpatient ward of the Pekalongan District Hospital were infection cases, most of them had normal nutritional status, but 28.1% were malnourished/poor.